Repetition and Reputation: Implications for Trust and Trustworthiness When Institutions Change - Bohnet, Iris; Huck, Steffen (American Economic Review, 2004)
Repetition and Reputation: Implications for Trust and Trustworthiness When Institutions Change by Iris Bohnet and Steffen Huck. Published in volume 94, issue 2, pages 362-366 of American Economic Review, May 2004